Development of PjBL–ESD E-Module to Improve Disaster Literacy for Higher Education Students - Herdini Herdini; Abdullah Abdullah; Erviyenni Erviyenni; Betty Holiwarni; Putri Adita Wulandari; Siti Nazhifah; Tiara Swastika Putri (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2026)
The relatively low level of students’ disaster literacy indicates that disaster education in higher education has not yet been optimally implemented, particularly due to lecturer-centered approaches, limited contextual learning, and insufficient use of digital learning resources. This study aimed to develop and evaluate the validity, practicality, and preliminary effectiveness of an e-module based on Project-Based Learning integrated with Education for Sustainable Development (PjBL–ESD) to enhance students’ disaster literacy. This study employed a Research and Development (R&D) method using the 4-D model. The validity of the e-module was assessed through expert review covering content, media, and pedagogical aspects. Practicality was evaluated through questionnaires administered to lecturers and students, focusing on ease of access, time efficiency, and ease of use. The preliminary effectiveness test involved a one-group pretest–posttest design analyzed using a paired-sample t-test. The effectiveness test involved 38 students enrolled in the Environmental Science and Disaster Mitigation course. The results showed that the PjBL–ESD e-module achieved a very high level of validity (≥96%) and demonstrated excellent practicality, with average scores of 98.40% from lecturers and 98.54% from students. The effectiveness test indicated a statistically significant improvement in disaster literacy, with the mean score increasing from 49.14 (pretest) to 81.74 (posttest) (p < 0.05). These results suggest that the PjBL–ESD e-module is valid, practical, and has strong potential to improve students’ disaster literacy within the context of this study. However, the lack of a control group inherent in the one-group pretest–posttest design constrains the extent to which causal conclusions can be drawn. This study implies that the integration of PjBL and ESD in digital modules can support more contextual and student-centered learning, particularly for disaster mitigation education in higher education.